Clinical characteristics and prognostic significance of immunoglobulin isotype switch in patients with multiple myeloma - Minqiu Lu; Bin Chu; Yutong Wang; Lei Shi; Shan Gao; Lijuan Fang; Qiuqing Xiang; Xi Liu; Yuehua Ding; Yuan Chen; Xin Zhao; Mengzhen Wang; et al. (Cancer Pathogenesis and Therapy, 2023)
Immunoglobulin (Ig) isotype switching in multiple myeloma (MM) is a rare form of clonal evolution. The aim of this study was to investigate the clinical features and prognostic significance of Ig isotype switching by observing Ig transformation in patients with relapse. A retrospective analysis was performed on 506 patients with newly diagnosed MM who were treated at our hospital from February 2005 to February 2020. The patients who experienced relapse were divided into the following four groups according to Ig phenotype: original paraprotein, complete isotype switching, light chain escape (LCE),and non-secretory clinical relapse. For comparative purposes with the original paraprotein group, the last three groups were pooled as the transformation group. Among the 506 included patients, 376 (74.3%) relapsed. Among them, 13/376 (3.5%) patients exhibited Ig isotype switching, including 3 with complete isotype switching, 3 with LCE, and 7 with non-secretory clinical relapse. Eleven remained sensitive to therapy, exhibiting at least a partial response. Seven patients survived for at least 20 months after relapse. The median overall survival time of the LCE, clinical relapse, and complete isotype switching groups were 6, 20, and 76 months, respectively, after recurrence. The clinical manifestations and Ig phenotypes of MM recurrence were different from those at the initial diagnosis in the 13 patients exhibiting Ig isotype switching. These differences vividly conveyed the heterogeneity of the clonal populations and provides direct clinical evidence for MM clonal evolution.